Using Mobile Application Intercessions to Decrease Prenatal Mortality in Developing Countries: A Systematic Review - Lim, Chen Kim; Tan, Kian Lam; Haufiku, Martin Shafiihuna (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Mobile phones are increasingly used in health systems in developing countries, and innovative technology solutions have great potential to overcome barriers of access to maternal health care. The objective of this study is to conduct a systematic review of the literature to ascertain what evidence exists for the effectiveness of mobile applications to decrease prenatal mortality through behavioural modification in developing countries. The study is essential in examining and illuminating certain aspects of the usage of mobile applications to improve prenatal care in developing areas and would, therefore, open up immense possibilities for prenatal care applications to improve essential precautional maternal services and in turn possibly lower the mortality rate in developing countries. Database searches and an intensive screening process were conducted before reviewing the full text of 34 articles and finally, nine articles that met all the inclusion criteria were selected. The study found that most of the included studies utilised text message suggestions to impact persistent conduct change in patients and all led in African nations. The review concluded that every one of the written reports appeared at any rate to show some proof of viability at changing conduct to decrease prenatal mortality. The policy infrastructure for funding, coordinating and guiding the sustainable adoption of precautional maternal services remains under-developed and that the integration of mobile health for prenatal health services has demonstrated positive outcomes.